THE PENAL CODE REFORMULATION IN ERADICATION OF NARCOTICS CRIME - Ginting, Iwan (Tadulako Law Review, 2017)
The high penalty of imposed fines aims to provide a deterrent effect and fear, both for the perpetrator of the criminal itself and for others. However, with the formulation of high penalty penalty threats and the granting of the possibility by the Act to replace the implementation of a fine with a subpoena of imprisonment in a short time cause the fine penalty in Law Number 35 Year 2009 is not effective.